Federal state differentials in the efficiency of health production in Germany: an artifact of spatial dependence? - Stefan Felder; Harald Tauchmann (The European Journal of Health Economics, 2013)
Due to regional competition and patient migration, the efficiency of healthcare provision at the regional level is subject to spatial dependence. We address this issue by applying a spatial autoregressive model to longitudinal data from Germany at the district (`Kreis') level. The empirical model is specified to explain efficiency scores, which we derive through non-parametric order-m efficiency analysis of regional health production. The focus is on the role of health policy of federal states (`Bundesländer') for district efficiency. Regression results reveal significant spatial spillover effects. Notably, accounting for spatial dependence does not decrease but increases the estimated effect of federal states on district efficiency. It appears that genuinely more efficient states are less affected by positive efficiency spillovers, so that taking into account spatial dependence clarifies the importance of health policy at the state level.
Keywords: I12; R10; 330; Health production; Order-m efficiency; Spatial autoregressive model